KETIKA ALAM DAN PEREMPUAN LEMBAH BALIEM DIPERKOSA OLEH ANTROPOSENTRISME KAPITALIS: KAJIAN EKOFEMINISME DALAM NOVEL TANAH TABU - Moh. Badrus Solichin (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
This research was conducted to investigate capitalistic anthropocentrism to nature and woman in Tanah Tabu. Here, Freeport is an actor of capitalistic anthropocentrism while Baliem Valley and female character in Tanah Tabu are representatives of exploited objects. By analysis, the theory of ecofeminism by Vandana Shiva is used here to answer the questions of the research. Therefore, the implication is to study act of capitalistic anthropocentrism of Freeport examined based on the purpose of western colonialism (United Stated of America) that came to Papua by developing mining industry. In the process, the mining industry run by capitalist faced the problem being tried to solve by using modern science and spirit of developing civilization as an effort to cover their act. In this case, ecofeminism shows role of women in struggling their exploited home (nature). This fact appears from relationship between women’s domestic life and nature that cannot be vanished.The discussion results in this study is firstly, the character of capitalistic anthropocentrism by Freeport is known from their motives in developing civilization by modern science, modernism toward conservatism, and colonialism. Secondly, ecofeminism puts female character Tanah Tabu in dualism of role; as a victim and a fighter against capitalistic anthropocentrism. Lastly, the reason why the female character is presented here is because ecofeminism views nature is as a woman who is pregnant and delivers life.